1998
DOI: 10.3168/jds.s0022-0302(98)75588-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Regulating Prostaglandin F2 Secretion from the Bovine Endometrium

Abstract: The mechanism that regulates luteolytic PGF2 alpha secretion as stimulated by oxytocin is thought to involve induction of the inositol (1,4,5)-trisphosphate-diacylglycerol second messenger system, which mobilizes intracellular calcium and activates protein kinase C. In Experiment 1, endometrial explants taken from heifers on d 18.5 to 19.5 postestrus had increased PGF2 alpha secretion after treatment with 1 microM calcium ionophore A23187 to increase intracellular calcium, 100 nM phorbol 12-myristate 13-acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
11
0
4
Order By: Relevance
“…The uterine response to OT depends on expression of OTR mRNA and protein [7,[17][18][19] and on generation of the second messengers inositol triposhate and diacyloglycerol [7,18,20,21]. OT also stimulates PGF2α secretion from the bovine endometrium through a previously discussed signaling pathway [22][23][24][25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The uterine response to OT depends on expression of OTR mRNA and protein [7,[17][18][19] and on generation of the second messengers inositol triposhate and diacyloglycerol [7,18,20,21]. OT also stimulates PGF2α secretion from the bovine endometrium through a previously discussed signaling pathway [22][23][24][25].…”
mentioning
confidence: 99%
“…The uterine response to OT depends on expression of OTR mRNA and protein [7,[17][18][19] and on generation of the second messengers inositol triposhate and diacyloglycerol [7,18,20,21]. OT also stimulates PGF2α secretion from the bovine endometrium through a previously discussed signaling pathway [22][23][24][25].It has previously been shown that OT acts on the porcine endometrium as a regulator of secretion of both luteolytic PGF2α [3,6] and luteotrophic PGE2 [6]. Progesterone (P4) inhibits OTstimulated production of endometrial and myometrial PG via mechanisms including regulation of OTR expression, inositol phosphate accumulation and intracellular Ca 2+ response [7,19,26,27].…”
mentioning
confidence: 99%
“…A ligação da ocitocina (OT) ao seu receptor aciona uma complexa via de síntese de PGF2α (MCCRACKEN; CUSTER; LAMSA, 1999). Os OXTRs são receptores acoplados à proteína Gqα, sua ativação estimula a fosfolipase C (PLC) que atua na membrana celular hidrolisando fosfatidil-inositol bisfosfato em Inositol 1,4,5 trifosfato (IP3) e 1,2 diacilglicerol (DAG) (TYSSELING et al, 1997 quinases reguladas por sinal extracelular (ERK1/2) e fosfolipase A2 (PLA2).…”
Section: Introductionunclassified
“…The calcium ionophore A23187 (CaI) promotes calcium flux across membranes and activates PLA 2 . It can also stimulate PG synthesis in the bovine endometrium (Danet-Desnoyers et al 1995, Tysseling et al 1998.…”
Section: Introductionmentioning
confidence: 99%